A red-shifted two-photon-only caging group for three-dimensional photorelease - Bartel, Yvonne; Dreuw, Andreas (Chemical science, 2018)
Based on nitrodibenzofuran (NDBF) a new photocage with higher two-photon action cross section and red-shifted absorption was developed. Due to calculations, a dimethylamino functionality (DMA) was added at ring position 7. The uncaging of nucleobases after two-photon excitation (2PE) could be visualized via double-strand displacement in a hydrogel. With this assay we achieved three-dimensional photorelease of DMA-NDBF-protected DNA orthogonal to NDBF-protected strands. While being an excellent 2P-cage, DMA-NDBF is surprisingly stable under visible-light one-photon excitation (1PE). This case of excitation-specific photochemistry enhances the scope of orthogonal photoregulation.
Gesehen am 10.03.2020